(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The developed working body is dedicated to the kinematic analysis of the construction of forced oscillating chisel-cultivator in an analytical method. As a result of the research, the analytical method of the movement of the joints of the mechanism generating forced vibrations was developed and its analysis was carried out.